Embodied Leadership the Somatic approach to developing your leadership - Hamill, Pete (London Kogan Page Limited, 2013)
Leaders don't just need to know about leadership -- leaders need to embody the capacity to lead in the midst of ambiguity and complexity. Developed by the Strozzi Institute in Northern California, the concept of embodied leadership is derived from somatic coaching, a unique approach that brings the body forward as an advocate in creating a place for change and transformation. It brings together language, action, feeling and meaning and is based on the idea that the mind and body are inextricably linked: to develop one, a person must cultivate the other.
Includes bibliographical references and index
Keywords: Leadership